ANALYSIS OF MODERN APPROACHES TO FORMATION OF PROFESSIONAL AND COMMUNICATIVE COMPETENCE OF FUTURE SPECIALISTS IN SOCIAL WORK - Віта Баранюк (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The main approaches of scientists to the formation of professional communicative competence in training of future specialists in social work are analyzed in the article. Basic individual psychological and social factors such as communication experience, learning of social roles, development of social value systems, motivation of an individual for professional communication activity, professional vocation and professional identity, which influence the formation of communicative competence are defined and characterized. The features of combination of competence and personal activity approaches in study process, as important factors in effective formation of professional and communicative competence of a future specialist in social work have been analyzed in this research.